2022
DOI: 10.1002/jsfa.11932
|View full text |Cite
|
Sign up to set email alerts
|

Residue analysis, dissipation patterns of chlorfenapyr, diafenthiuron and their corresponding metabolites in tea trees, and dietary intake risk assessment

Abstract: BACKGROUND: Recently, chlorfenapyr and diafenthiuron have been widely used to prevent and control diseases and pests in tea production. However, rare studies have investigated the dissipation patterns of chlorfenapyr, diafenthiuron and their metabolites simultaneously in tea matrices. Here, we established an analytical method to investigate the degradation patterns of five target compounds in tea shoots and made tea samples. Moreover, the dietary intake risk assessment of chlorfenapyrdiafenthiuron mixture amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
(79 reference statements)
0
3
0
Order By: Relevance
“…However, diafenthiuron is easily degraded to diafenthiuron–urea and diafenthiuron–methanimidamide in plants, which are considered to have higher toxicity than the parent pesticides. These metabolites accumulate in the lung and liver, thereby threatening human health . Wu et al indicated that the chronic hazard quotient of diafenthiuron and its metabolites was high and caused an unacceptable health risk to tea consumers due to the high residue and low ADI, even though there was a lower transfer rate in tea infusion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, diafenthiuron is easily degraded to diafenthiuron–urea and diafenthiuron–methanimidamide in plants, which are considered to have higher toxicity than the parent pesticides. These metabolites accumulate in the lung and liver, thereby threatening human health . Wu et al indicated that the chronic hazard quotient of diafenthiuron and its metabolites was high and caused an unacceptable health risk to tea consumers due to the high residue and low ADI, even though there was a lower transfer rate in tea infusion.…”
Section: Resultsmentioning
confidence: 99%
“…These metabolites accumulate in the lung and liver, thereby threatening human health. 57 Wu et al 41 indicated that the chronic hazard quotient of diafenthiuron and its metabolites was high and caused an unacceptable health risk to tea consumers due to the high residue and low ADI, even though there was a lower transfer rate in tea infusion. In addition, these metabolites could be detected after 21 days, revealing that they were persistent in tea plants.…”
Section: Analytical Chemistrymentioning
confidence: 99%
“…8 Moreover, in mammals the decomposition products of DIAF are toxic to target organs such as the liver and lungs, and the widespread use of DIAF will inevitably lead to environmental pollution and threaten human health. 9,10 Cabbage is a widely used and popular cruciferous vegetable, which is also an important ingredient in Chinese sauerkraut. 11,12 Apples are a rich source of bioactive compounds and micronutrients that are essential for a normal diet.…”
Section: Introductionmentioning
confidence: 99%
“…Tea weevils are currently controlled primarily via the application of chemical insecticides. However, using chemical insecticides may lead to an increased risk of pesticide residues in tea and tea products (Xu et al 2022). In addition, some of these chemicals are potentially harmful to non-target beneficial organisms, with inevitable detrimental effects on the environment (Sutar et al 2022).…”
Section: Introductionmentioning
confidence: 99%